Phoneme based Dialect variation of Assamese Language - Sharma, Bitopi; Talukdar, P.H (International Journal of Computer Sciences and Engineering, 2018)
The Assamese language is broadly classified in three major eras viz- early Assamese period, middle Assamese and modern Assamese. Influence of Sanskrit and the Magadhi Prakrit is visible in the vocabulary of the language. Banikanta Kakati has broadly classified the Assamese language into two divisions –namely Eastern Assamese and Western Assamese. Understanding the difference in the phonology, play an important role in the development of emotional TTS. (MFCC) is most popular features of speech recognition. This is a feature of vocal tract. Here the variations on this process are observed using MFCC. MFCC plays an important role in identifying speakers.